SÉRIES ORIGINAIS DA NETFLIX: ALTERAÇÕES NA ESTRUTURA NARRATIVA NO CONTEXTO DO BINGE-PUBLISHING - CORRÊA, ANGELA MIGUEL (2019)
This dissertation aims to identify possible changes in the narrative structure of Netflix Originals series, productions available to subscribers through binge-publishing, a distribution model of the streaming platform in which all episodes are released at once. For this purpose, this essay is based on authors such as Raymond Williams, Arlindo Machado, Amanda Lotz, Jason Mittell and Esther Van Ede to map the evolution of television and its transformations by adopting technologies such as VCR and streaming, identifying narrative elements present in contemporary serial fictions made by and for TV, and contextualize Netflix as a paradigmatic case in the audiovisual industry. As a methodological proposal, this research starts from a content analysis and the categorization of narrative elements to indicate possible changes present in the science fiction series Netflix Originals Sense8 (USA, 2015), 3% (Brazil, 2016) and Dark (Germany, 2017 ). Among the six analyzed categories (erotetic narration, multiplicity of plots, space-time conception, episodic-serial format, gaps and recaps), we found alterations in the use of narrative gaps and recaps.